Santri Mengajar: The Amaliyah Tadris Model in Shaping the Spirit and Teaching Skills at Nurul Hakim Islamic Boarding School, West Lombok - Baiq Ninda Auliya; Muhammad Muhammad; Emawati Emawati (Prodi PAI STIT Sunan Giri Bima, 2026)
This study aims to analyze the